Análise da cultura de segurança e do ambiente de trabalho dos profissionais de enfermagem em um hospital de médio porte - CÁTIA TEIXEIRA DA ROCHA (2022)
The hospital environment, favorable to the performance of practices by the nursing team, is considered essential for the satisfaction of professionals who work there, and for achieving a favorable safety culture. Knowing the perception of nursing professionals in relation to their work environment is essential, as it allows managers to establish strategies to improve stressors and, consequently, promote safe care for patients and their families. The objective of this study was to analyze the safety culture and the work environment of nursing professionals in a medium-sized hospital. Observational, cross-sectional, descriptive study with a quantitative approach. The research was carried out in the care units of a medium-complexity hospital, located in the municipality of Três Lagoas, eastern region of the state of Mato Grosso do Sul, using the instruments (1) sociodemographic and professional characterization; (2) Nursing Work Index (NWI-R) nurses; (3) Nursing Work Index (NWI-R) for nursing assistants and technicians; (4) Hospital Survey on Patient Safety Culture (HSOPSC). Data were collected from October 2021 to February 2022, and the universe of this study was composed of professionals from the nursing team, who worked with direct nursing care for patients and/or were coordinators/supervisors of care units. The final sample consisted of 51 participants, 14 of whom were nurses and 37 Nursing Technicians/Aides (TE/AE). The data obtained were analyzed by the free software R (version 4.1.1), however the main statistical analysis used was of the descriptive type. A comparison was made between the scores obtained by nurses and TE/AE for each subscale of the NWI-R using the nonparametric Mann-Whitney test. The assessment of the NWI-R instrument was based on reference, with values equal to or less than 2.5 indicating a favorable environment for the practice. In the HSOPSC, the evaluation was carried out considering as a strengthened dimension the one with positive responses greater than or equal to 75% and the weakened dimension when the percentage of positive responses is less than or equal to 50%. The work environment, in the perception of nursing professionals, was considered unfavorable, since the general average of the subscales was 2.6. The autonomy and organizational support subscales received higher scores among nursing professionals, with an average of 2.61 and 2.63, respectively. “Environmental control” was evaluated positively, 2.5. When comparing the answers obtained by the professional categories studied, there was no statistically significant difference. Regarding the Patient Safety Culture (CSP), no dimension was identified as strengthened in the institution (>75%) and of the 12 dimensions evaluated, it was observed that the dimensions "teamwork", "expectations and actions of the unit/service management/supervision that favor safety” “organizational learning/continuous improvement”, “hospital management support for patient safety” and “frequency of reported events” presented a percentage >50% and have potential for improvement, after implementing measures that promote patient safety. The results obtained indicate that the work environment and the CSP of the studied institution are unfavorable, in the perception of nursing professionals. It is believed that active leaderships are essential for positive changes to take place within the hospital environment, as well as for the installation of a favorable CSP.